Gender Differences in Self-Reported Symptoms of Depression among Patients with Acute Coronary Syndrome. (26th March 2012) - Frazier, Lorraine; Yu, Erica; Sanner, Jennifer; Liu, Fang; Udtha, Malini; Cron, Stanley; Coulter, Stephanie; Bogaev, Roberta C.
Abstract : This study examined the prevalence of self-reported depressive symptoms and the self reported somatic depressive symptoms as measured by the Beck Depression Inventory-II (BDI-II) among patients hospitalized for acute coronary syndrome (ACS), and explored the impact of gender on both. A convenience sample of 789 adults (248 women and 541 men) was recruited for the study during hospital admission for ACS and participants were screened for self-reported depressive symptoms. BDI-II scores of ≥14 indicate a moderate level of depressive symptoms and this cut-off score was used to categorize patients into depressed and non-depressed groups. Pearson chi-square tests for independence (categorical variables) and t tests for independent samples (continuous variables) were used for gender comparisons. Results showed that depressive symptoms during ACS episodes were different between women and men. Women reported greater overall depressive symptoms (BDI-II mean = 11.89, S.D. = 9.68) than men (BDI-II mean = 9.00, S.D. = 7.93) (P < 0.000 ). Significantly more women (7.66%) were identified positive for somatic depressive symptoms (sleep and appetite disturbances and fatigue) than men (2.22%) (P = 0.0003 ). Findings support that there are gender differences in depressive symptoms experienced by patients hospitalized for ACS. Somatic symptoms of depression may be important indicators of depression especially among female ACS patients.